COMPARISON OF SUBARACHNOID MAGNESIUM SULFATE AND FENTANYL AS ADJUVANTS WITH 0.5% HEAVY BUPIVACAINE FOR POSTOPERATIVE ANALGESIA IN INFRA-UMBILICAL SURGERIES - KAUR, GAGANDEEP; HUSAIN RIZVI, SYED ZEESHAN; SRIVASTAVA, RAJ KRISHNA; RANA, ABHAY KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objective of the study was to compare the efficacy of adjuvant use of subarachnoid fentanyl with the adjuvant use of subarachnoid magnesium sulfate as adjuvants to bupivacaine in subarachnoid block for infraumbilical surgeries in terms of: (1) Block characteristics, namely, time taken for onset of block and time taken for regression of block, (2) Hemodynamic stability in intra- and post-operative phase. Methods: A total of 70 ASA I/II patients scheduled for infra-umbilical surgery were enrolled in the study and were randomized either to Group F (0.5 mL Fentanyl+3 mL 0.5% Bupivacaine) (n=35) or to Group M (0.5 mL 20% Magnesium sulfate+3 mL 0.5% Bupivacaine). Time to achieve onset of block, duration of block. Data were analyzed using the Chi-square and Independent samples, t’-test. Results: Age of patients ranged from 18 to 55 years. The two groups were matched onset of sensory and motor block was significantly earlier in Magnesium sulfate group as compared to fentanyl group. Regression of motor and sensory block was significantly earlier in group where magnesium sulfate was used as an additive in contrast to fentanyl. No other complication except nausea (8.6%) and bradycardia (8.6%) was reported in any of the patient. Conclusion: Although magnesium sulfate appears to be a relatively safer alternative than fentanyl for adjuvant use with hyperbaric bupivacaine for post-operative pain management and to facilitate better block characteristics; however, it fails to achieve the analgesic effect even comparable to fentanyl. Further studies with inclusion of a control group and with changed drug–dose combinations are recommended to find out a better alternative.